Opposite monosynaptic scaling of BLP–vCA1 inputs governs hopefulness- and helplessness-modulated spatial learning and memory - Ying Yang (Nature Portfolio, 2016)
How emotions affect memory is an open question. Here the authors establish learnt hopeful and learnt helpless mouse models, and find that posterior basolateral amygdala to ventral hippocampal CA1 monosynaptic glutamatergic inputs link emotions to spatial memory performance.